Du bon usage de la vodka - Philippe Mennecier (Revue d'ethnoécologie)
Vodka culture is very different from that of wine. Vodka does not differ according to the regions, and it has not any particular flavour: they don’t drink it for the pleasure of its taste, but for its effects. An almost immutable ritual offers partaking and maintaining a pleasant collective inebriation. The codified succession of the toasts, called by accepted formulas, strengthen guest’ cohesion.